Health disparities in preterm births - Brown, Judy; Chang, Xiaolin; Matson, Adam; Lainwala, Shabnam; Chen, Ming-Hui; Cong, Xiaomei; Casavant, Sharon G. (Frontiers in Public Health, 2023)
Black African American (B/AA) women have a 2-fold to 3-fold elevated risk compared with non-Hispanic White (W) women for preterm birth. Further, preterm birth is the leading cause of mortality among B/AA infants, and among survivors, preterm infant adverse health outcomes occur disproportionately in B/AA infants. Racial inequities in maternal and infant health continue to pose a public health crisis despite the discovery >100 years ago. The purpose of this study was to expand on reported preterm infant outcome disparities. A life-course approach, accumulation of lifelong stress, may explain social factors causing preterm birth rate and outcome inequities in B/AA mothers. Anthropometric measures and clinical treatment information for 197 consented participants were milled from electronic health records across four years. The Neonatal Infant Stressor Scale was used to tally acute and chronic painful/stressful procedures. Neurobehavioral differences were investigated using the Neonatal Intensive Care Unit (NICU) Network Neurobehavioral Scale. B/AA mothers gave birth to preterm infants earlier than W mothers. NICU hospitalization stays were extended more than two weeks for the significantly smaller B/AA preterm infants in comparison to the age-matched W preterm infants. A higher number of chronic procedures with demonstrated altered stress response patterns were recorded for B/AA preterm infants. This cross-sectional analysis of preterm birth rates and preterm infant neurodevelopmental outcomes is presented in the context of NICU stress and pain, with attendant implications for infant mortality and future health disparities.